Analysis Of Difficulties In The Co-Education System Of Pakistan: A Gender Perspective - Saba Irshad (Asian Journal of Management, Entrepreneurship and Social Science, 2022)
Education brings desirable changes in human behaviour. The survival of any nation is not ensured without education as it becomes the cause of prosperity when the individuals of any society become familiar with it. Pakistan is far behind in the competition of education of an individual and especially women's education. Co-education refers to educating males and females in one setting. This type of learning has so many difficulties for the male and female while learning in the. Total population of the study was 145 students. A sample size of 105 students was determined by using the online website www.surveysystem.com. A well-structured interview schedule was developed to collect data. Gender inequality affects negatively the educational performance of female students. The confidence level of female students is negatively affected in the co-educational system. All the ethical concerns were kept intact throughout the research. The data were analyzed through software (SPSS). Finding and conclusion were reported in the form of a thesis according to the standard format of the University of Agriculture, Faisalabad. The majority 65.7 % of respondents’ were reported yes to the harassment in the co-educational institutions while around 34.3 % of the respondents answered no about the harassment in the co-educational institution. Female students feel hesitation and shyness while participating in co-educational classes Around 5.2 % of the respondents were strongly agree that there is hesitation and shyness in co-educational classes. While 33.3% of the respondents were agreed and 11.4 % of the respondents were undecided about the hesitation and shyness while participating in the coeducational classes